COVID-19–Associated Ischemic Stroke in a Patient on Therapeutic Anticoagulation - Scharpf, William (Neurologist, 2021)
The coronavirus disease 2019 (COVID-19) has been associated with a hypercoagulable state, increasing the risk for ischemic stroke. In select cases, patients are already on anticoagulation therapy. Such examples highlight the severity of COVID-19’s hyperthrombotic state, and raise questions regarding optimal stroke prevention in these patients. CASE REPORT: An 84-year-ool male with past medical history of chronic obstructive pulmonary disease, hypertension, and paroxysmal atrial fibrillation was admitted for respiratory failure secondary to COVID-19 pneumonia. He was continued on his home apixaban 5 mg twice daily. On day 2 of admission, he developed a new aphasia, and right-sided facial droop. Computed tomography (CT) head was unrevealing. CT angiography did not show large vessel occlusion. CT perfusion demonstrated a left middle cerebral artery ischemic penumbra, without core. He was not eligible for thrombolysis or thrombectomy interventions. Later CT head confirmed L middle cerebral artery infarct. The patient’s D-dimer was 1,184 ng/mL on day 1 of admission, and increased to 111,574 by day 4. His hypoxia worsened, requiring intubation and transfer to the ICU. He experienced further clinical decline and eventual demise. CONCLUSION: Ischemic stroke in anticoagulated patients with COVID-19 has been previously reported. Such cases emphasize the severity of the coronavirus virus associated hypercoagulable state. A majority of reported cases have occurred in patients continuing their ambulatory therapy. Overall, such cases are likely underreported. There are current trials comparing therapeutic versus prophylactic dose anticoagulation in patients with COVID-19. There are no studies specifically addressing anticoagulation agent failure in these patients. Further research is required this area to determine the optimal therapy for patients with COVID-19.